Experimental membrane fouling sensors - Ting, Wee Lin. (2011)
Of late, one of the crucial issues that prohibited the successful application of ultrafiltration (UF) in water treatment process is primarily due to the fouling of membrane by natural organic matter (NOM). Fouling causes flux decline and increase in resistance due to internal pore adsorption, progressive pore blocking and cake formation on the surface of membrane. Fouling is commonly believed to have negative effects on the efficiency, permeate quality and operational cost of UF membranes.In this study, the author hopes to contribute to the understanding of the occurrence of fouling in submerged dead-end ultrafiltration (UF) hollow fibre membrane system by organic foulants. The experiment is carried out under different concentrations, low pressure and steady flux operating conditions. Humic acid sodium salt which is a significant organic foulant is used as the model foulant representative of NOM. When fouling occurs progressively as time increases, resistance also increases resulting in a larger TMP required to maintain a higher value constant flux. This experiment also demonstrated that for a higher concentration organic foulant, the critical flux will be lower which means that a shorter period of time is required for fouling to occur. A fouling index which can be used to predict the likelihood of the occurrence of fouling under constant flux operations will be determined based on the experimental data obtained.